Determination of BRCAness phenotype in breast tumors for the appointment of neoadjuvant chemotherapy based on platinum and taxanes - Tsyganov, Matvey M.; Ibragimova, Marina K.; Garbukov, Evgeny Yu; Bragina, Olga D.; Karchevskaya, Ariana A.; Usynin, Evgeny A.; Litvyakov, Nicolay V. (International journal of molecular sciences)
The concept of BRCAness was developed because of similarities between sporadic and hereditary breast cancer. BRCAness defines the pathogenesis and treatment sensitivity of many types of cancer, as well as the presence of a defect in the homologous recombination repair of tumor cells simulating the loss of BRCA1 or BRCA2, as in the presence of germline mutations. The question of treatment effectiveness for BRCA-like tumors is controversial and open. Thus, the aim of this work was to study the effectiveness of neoadjuvant chemotherapy (NAC) in BRCA-deficient breast cancer patients without germline mutations. The study involved 130 patients with breast cancer in stages IIA–IIIB. The treatment regimen included neoadjuvant chemotherapy, surgery, and adjuvant chemotherapy. The materials used were tumor samples from before and after chemotherapy. DNA and RNA were isolated from the tumor material. RNA was used to assess the expression level of BRCA1, while DNA was used for methyl-sensitive PCR. A microarray analysis was performed on high-density DNA chips from an Affymetrix CytoScanTM HD Array to assess DNA copy number aberration (CNA status) and loss of heterozygosity. A statistical analysis was performed using the Statistica 8.0 application package. It was noted that the existence of copy number aberrations in genes was statistically significantly associated with tumor treatment response and disease prognosis. Patients with partial regression had a statistically significantly higher amount of deletion than patients without an objective response (5/25 patients; 16%), as shown in the general sample of patients (52.9% versus 27.1%, respectively) at p = 0.0001 and in patients treated with anthracycline-containing regimen (p = 0.0001). In addition, it was shown that patients with BRCA1 deletion had higher rates of metastatic-free survival (log rank test, p = 0.009). BRCAness patients had a higher rate of 5-year metastatic survival, but not of treatment efficacy. The prospective study showed the positive effect of assessing the BRCAness phenotype of a tumor before treatment and of prescribing personalized NAC regimens. The objective response rate was statistically significantly more often observed in the group of patients with personalized chemotherapy (85.0% (34/40 patients) versus 62.3% (56/90 patients); p = 0.007). Despite the controversial effectiveness of BRCA-like tumor treatment, our data showed high predictive and prognostic significance of the BRCAness phenotype for the personalization of platinum and taxane regimens.